Reação de desinserção em SbxCoSb3-x - Miotto, Fernanda (My University, 2014)
The compound SbxCoSb3-x was produced at high pressures and high temperatures in a self-insertion reaction from the binary skutterudite CoSb3. The self-insertion reaction is characterized by the collapse of Sb atoms to the 2a site, into the cage formed by the Co and Sb atoms in the skutterudite structure. The opposite reaction, i.e., Sb desinsertion, occurs when the SbxCoSb3-x compound is heated at room pressure. This desinsertion reaction was followed by means of differential scanning calorimetry (DSC), X-ray diffraction (XRD) and electrical resistivity measurements, and its study constitutes the main objective of this work. The CoSb3 sample was synthesized as described in the literature. The synthesis was confirmed by XRD, and the presence of contaminant phases was not observed. Cylindrical samples of the SbxCoSb3-x phase were obtained by submitting CoSb3 at pressures of 7.7 GPa and temperatures up to 550ºC, with the aid of a toroidal high pressure cell available at the Laboratório de Altas Pressões e Materiais Avançados - LAPMA in the Instituto de Física of the Universidade Federal do Rio Grande do Sul - IF/UFRGS. The presence of the SbxCoSb3-x phase was confirmed by XRD analysis. In order to determine the electrical resistivity of samples rich in SbxCoSb3-x phase, a DC system was developed which is applicable to small volume cylindrical samples such as those obtained at high pressures and high temperatures. The calibration of the DC system was made by measurements of the electrical resistivity of reference materials (NIST-SRM 1461 and NIST-SRM 8426). The DSC measurements revealed the presence of two thermal events. An endothermic peak was observed at 118ºC which is not associated to structural changes neither significant variation in the electrical resistivity. The exothermic event that starts at 180ºC is the signature of the desinsertion of Sb atoms from the skutterudite cage, as verified by XRD analysis and electrical measurements. After heating to 350°C, the sample rich in the SbxCoSb3-x phase converts back to the stable phase, CoSb3. The desinsertion reaction follows a first-order kinetics, with a transition enthalpy of approximately 50 J/g and an activation energy of 83 kJ/mol. The electrical resistivity at room temperature of samples rich in SbxCoSb3-x is about ten times smaller than that of CoSb3. This result, along with a possible low thermal conductivity, suggests that SbxCoSb3-x may constitute a high performance thermoelectric material.
O composto SbxCoSb3-x foi produzido em altas pressões e altas temperaturas em uma reação de auto-inserção a partir da escuterudita binária CoSb3. A reação de auto-inserção é caracterizada pelo colapso de átomos de Sb para o sítio 2a, no interior das cavidades formadas pelos átomos de Co e Sb na estrutura da escuterudita. A reação inversa, de desinserção de Sb, ocorre quando o composto SbxCoSb3-x é aquecido à pressão ambiente. O acompanhamento desta reação de desinserção por meio de medidas de calorimetria exploratória diferencial (DSC), difração de raios X (DRX) e de resistividade elétrica constitui o objetivo principal deste trabalho. A amostra de CoSb3 foi sintetizada conforme rota proposta pela literatura. A síntese foi confirmada por meio de DRX, e não foi observada a presença de fases contaminantes. Amostras cilíndricas da fase SbxCoSb3-x foram obtidas submetendo CoSb3 a pressões de 7,7 GPa e temperaturas de até 550ºC, com o auxílio de prensas hidráulicas e câmaras toroidais disponíveis no Laboratório de Altas Pressões e Materiais Avançados LAPMA no Instituto de Física da Universidade Federal do Rio Grande do Sul IF/UFRGS. A presença da fase SbxCoSb3-x foi comprovada por meio de análises de DRX. Para determinação da resistividade elétrica de amostras ricas de fase SbxCoSb3-x foi desenvolvido um sistema DC, aplicável a amostras cilíndricas de pequeno volume tal como as obtidas em altas pressões e altas temperaturas. A aferição do sistema foi feita através de medidas de resistividade elétrica de materiais de referência (NIST-SRM 1461 e NIST-SRM 8426). As medidas de DSC revelaram a presença de dois eventos térmicos. Um pico endotérmico foi observado em 118ºC e não está associado a alterações estruturais e nem a variações significativas na resistividade elétrica. O evento exotérmico, que inicia em 180ºC, constitui a assinatura da desinserção dos átomos de Sb do interior da escuterudita, como verificado por análises de DRX e medidas elétricas. Após aquecimento até 350ºC, a amostra rica na fase SbxCoSb3-x retorna à fase estável, CoSb3. A reação de desinserção obedece a uma cinética de primeira ordem, cuja entalpia de transição é de aproximadamente 50 J /g e uma energia de ativação de 83 kJ/mol. A resistividade elétrica à temperatura ambiente de amostras ricas em SbxCoSb3-x é cerca de dez vezes inferior à do CoSb3. Este resultado, aliado possivelmente a uma baixa condutividade térmica, sugere que a fase de auto-inserção SbxCoSb3-x pode constituir um material termoelétrico de alto desempenho.
Keywords: Engenharia de materiais e metalúrgica; Escuterudita; Altas pressões e altas temperaturas; Materiais termoelétricos; Difração de raios X; Calorimetria exploratória diferencial; Resistividade elétrica; Termodinâmica; Skutterudite; High pressures and high temperatures; Thermoelectric materials; X-ray diffraction; Differential scanning calorimetry; Electrical resistivity; Thermodynamics